Association between dust particulate and occupational rhinitis among basement parking lot workers in Jakarta - Niken Lestari Poerbonegoro; Setyawati Budiningsih; Rina Metalapa (PERHATI-KL, 2018)
Background: Jakarta municipal government estimates that at least 70% of Jakarta air pollution comes from traffic and vehicles. The prevalence of occupational rhinitis increases in such polluted environment. History of atopic disease and smoking habit might aggravate this condition. Purpose: To determine the association between dust particulate matter exposure and occupational rhinitis among basement parking lot workers in Jakarta. Methods: A cross-sectional study was performed on 57 workers from December 2014 until March 2015. Questionnaires on nasal symptoms and eosinophil counts by nasal mucosal scrapings were collected before and after working-hours to evaluate occupational rhinitis. Level of dust particulate matter was measured using high volume air sampler, and calculated by gravimetric method. Results: Three workers were diagnosed with occupational rhinitis (5.2%). Level of dust particulate matter was below permitted level in studied basement parking lots. There was no significant association between occupational rhinitis and working period (OR 0.5 [95% CI 0.43 to 5.85], p=1.000) and workplace (OR 435 [95%CI =0.37-51.37], p=0.255). Increased eosinophil level was associated with the history of atopic disease (OR 23.33 [95%CI=2.40-224.62], p=0.001but not associated with smoking habit (OR 0.13 [95%CI=0.22-7.71], p=0.575). Conclusion: There was no significant association between dust particulate matter exposure and occupational rhinitis among basement parking lot workers. Despite the low level of dust particulate matter exposure, occupational rhinitis did occur. Latar Belakang: Pemerintah DKI Jakarta memperkirakan sekitar 70% polusi udara di Jakarta berasal dari lalu lintas dan kendaraan bermotor. Prevalensi Rinitis Akibat Kerja (RAK) cenderung meningkat pada lingkungan berpolusi. Riwayat atopi dan kebiasaan merokok dapat memperberat penyakit tersebut. Tujuan: mengetahui hubungan pajanan partikulat debu terhadap RAK pada pekerja area parkir basement di Jakarta. Metode: Studi potong lintang dilakukan terhadap 57 pekerja dari Desember 2014 sampai Maret 2015. Pengisian kuesioner gejala hidung dan hitung jumlah eosinofil kerokan mukosa hidung dilakukan sebelum dan sesudah jam kerja untuk evaluasi RAK. Kadar partikulat debu diukur dengan High Volume Air Sampler lalu dikalkulasi dengan metode gravimetrik. Hasil: Didapatkan 3 orang pekerja dengan diagnosis RAK (5,2%). Kadar pajanan partikulat debu di lokasi studi dibawah nilai ambang batas yang diizinkan. Tidak terdapat hubungan bermakna antara RAK dengan lama bekerja (OR 0,5 [95% CI 0,43- 5,85], p=1,000) dan tempat kerja (OR 435 [95%CI=0,37-51,37], p=0,255). Terdapat hubungan yang bermakna antara peningkatan kadar eosinofil dan riwayat atopi (OR 23,33 [95%CI=2,40-224,62], p=0,001), tetapi hubungan tidak bermakna ditemukan antara peningkatan kadar eosinophil dan kebiasaan merokok (OR 0,13 [95% CI=0,22-7,71], p=0.575). Kesimpulan: Tidak terdapat hubungan bermakna antara pajanan partikulat debu dan RAK pada pekerja area parkir basement. Pada kadar partikulat debu rendah, ternyata ditemukan pekerja dengan RAK.